Performance evaluation of scoring systems for predicting post‐operative hypertension cure in primary aldosteronism. (19th June 2021) - O'Toole, Samuel Matthew; Hornby, Catherine; Sze, Wing‐Chiu Candy; Hannon, Mark John; Akker, Scott Alexander; Druce, Maralyn Rose; Waterhouse, Mona; Dawnay, Anne; Sahdev, Anju; Matson, Matthew; Parvanta, Laila; Drake, William Martyn
Abstract: Objective: Hypertension cure following adrenalectomy in unilateral primary aldosteronism is not guaranteed. Its likelihood is associated with pre‐operative parameters, which have been variably combined in six different predictive scoring systems. The relative performance of these systems is currently unknown. The objective of this work was to identify the best performing scoring system for predicting hypertension cure following adrenalectomy for primary aldosteronism. Design: Retrospective analysis in a single tertiary referral centre. Patients: Eighty‐seven adult patients with unilateral primary aldosteronism who had undergone adrenalectomy between 2004 and 2018 for whom complete data sets were available to calculate all scoring systems. Measurements: Prediction of hypertension cure by each of the six scoring systems. Results: Hypertension cure was achieved in 36/87 (41.4%) patients within the first post‐operative year, which fell to 18/71 (25.4%) patients at final follow‐up (median 53 months, P  = .002). Analysis of receiver operating characteristic area under the curves for the different scoring systems identified a difference in performance at early, but not late, follow‐up. For all systems, the area under the curve was lower at early compared with late follow‐up and compared to performance in the cohorts in which they were originally defined. Conclusions: No single scoring system performed significantly better than all others when applied in our cohort, although two did display particular advantages. It remains to be determined how best such scoring systems can be incorporated into the routine clinical care of patients with PA.